Framework for Traditional Banks in SG to Assess and Compete with Rising Neo Banks and FinTechs - Venkatarathinam , Balasubramanian (Digital Repository of Theses, 2025)
The banking sector in Singapore is being disrupted by neo-banks and various FinTech companies, offering customer-centric, tech-driven innovations that no longer align with traditional banks' image. This study seeks to offer a framework through which traditional banks in Singapore will be able to assess and compete with these new digital-first players. The research is to identify the key factors that make the success of neo banks and FinTechs, the competitive pressure they impose on traditional banks, and assess the ability of the strategies of traditional banks to enhance customer satisfaction and market performance. The goals will be accomplished using a mixed-method approach that combines qualitative and quantitative data; the quantitative data collected from customer surveys and financial performance indicators, while the qualitative data is obtained from focus groups. In this study, the survey was carried out through online questionnaires to 300 respondents. The acquired data were analyzed using “IBM Statistical Package for Social Science” (IBM SPSS). Using this software, reliability analysis, frequency analysis, descriptive statistics, regression, and correlation tests were performed on the dataset. These methods were used by the study to assess the effect of neo banks and FinTechs on customer preferences, service expectations, and market performance metrics of traditional banks. According to the findings, traditional banks are under pressure to digitize further and use AI-driven solutions, as well as omnichannel service models, to be able to compete. Secondly, the study underscores the relevance of a strategic partnership between traditional banks and the professional FinTech firm to take advantage of digital breakthroughs and increase service offerings. Also, digital transformation projects can increase customer satisfaction, increase retention rates, and well as banking industry competitive positions. Theoretical and managerial implications of the study are forwarded on the need for a hybrid banking model that integrates technology-driven efficiencies with traditional banking strengths. It shows how continuous innovation, regulators' compliance and strategic collaboration are necessary for the long-term success in changing financial domain. Future research may determine, for instance, to what extent blockchain is an enabler of economic security in such hybrid banking, as well as customer trust in digital banking. Contribution to the study of the digital banking dynamics, this work discusses benefits and lessons for policymakers and industry managers, and researchers who are confronting the transformation of financial services.